2016
DOI: 10.1007/s10552-016-0814-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between meeting the WCRF/AICR cancer prevention recommendations and colorectal cancer incidence: results from the VITAL cohort

Abstract: Purpose In 2007 the World Cancer Research Fund (WCRF) and American Institute for Cancer Research (AICR) published eight recommendations regarding body weight, physical activity and dietary behaviors aimed at reducing cancer incidence worldwide. In this paper we assess whether meeting the WCRF/AICR recommendations is associated with lower CRC incidence; evaluate whether particular recommendations are most strongly associated with lower CRC incidence; and assess whether associations differ by sex. Methods We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 26 publications
2
37
1
2
Order By: Relevance
“…The EPIC study concluded that a one‐point increment in the WCRF/AICR score was associated with 12% reduced CRC risk . A US study found a 58% lower incidence of CRC risk for subjects meeting 4–6 WCRF/AICR recommendations compared to those meeting no recommendations . Another study in the US reported no association between the adherence to WCRF/AICR and CRC risk among African American women though they indicated that the adherence to WCRF/AICR recommendations was very low in the studied population.…”
Section: Discussionmentioning
confidence: 88%
“…The EPIC study concluded that a one‐point increment in the WCRF/AICR score was associated with 12% reduced CRC risk . A US study found a 58% lower incidence of CRC risk for subjects meeting 4–6 WCRF/AICR recommendations compared to those meeting no recommendations . Another study in the US reported no association between the adherence to WCRF/AICR and CRC risk among African American women though they indicated that the adherence to WCRF/AICR recommendations was very low in the studied population.…”
Section: Discussionmentioning
confidence: 88%
“…Each one-point increase in the score conferred a significant 34% to 58% lower risk for adhering to ≥1 recommendation or 5–6 recommendations respectively, compared to non-adherence. Corresponding results in women were 26% to 55% lower risk and 39% to 59% lower risk in men [39]**. Nomura et al and Makarem et al also calculated recommendation adherence scores in smaller cohort studies but found no association with colorectal cancer risk [40, 41].…”
Section: Resultsmentioning
confidence: 99%
“…Findings from these studies are summarized in Supplemental Table 1. The indices included the following: HEI in three studies [2729]; AHEI in two studies [27, 28]; DASH in three studies [27, 30, 31]; several versions of the Mediterranean dietary pattern in eight studies [27, 28, 30, 3236]; healthy Nordic food index in one study [37]; recommended food scores in two studies [28, 38]; WCRF/AICR score in four studies [2, 3941]; and dietary inflammatory index in seven studies [4248]. We included in this category, a study that derived four vegetarian dietary patterns based on a priori criteria [49].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have determined that diet, physical activity level, and body weight influence the incidence of colorectal cancer (CRC), the third most commonly diagnosed cancer in men and women in the United States . African Americans are at increased risk of developing CRC; incidence rates were approximately 21.8% higher among African Americans than whites in 2015 .…”
Section: Introductionmentioning
confidence: 99%